Structural Aspects of Reactive Organometallic Compounds - Silvia Schaffner; Markus Neuburger; Hans-Peter Weber; Margareta Zehnder (CHIMIA)
The structural chemistry and catalytic activity of palladium complexes with chiral or prochiral ligands and substrates has been investigated using a suite of techniques. In particular, solid-state structural characterization of complexes has provided a database from which a combination of theoretical and empirical methods are being used to parameterize the factors leading to high activity.